Diabetes Mellitus Increases the Risk of Bladder Cancer: An Updated Meta-Analysis of Observational Studies - Fang, Hong (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Increasing evidence suggests that diabetes mellitus (DM) may be associated with an increased risk of bladder cancer. We performed an updated meta-analysis to examine the association between DM and risk of bladder cancer. MATERIALS AND METHODS: We systematically searched the EMBASE and Medline (PubMed) databases (from inception through February 1, 2013) and reviewed the reference lists of relevant publications to search for additional studies. Summary relative risks (RRs) with 95% confidence intervals (CIs) were calculated with random-effects models. RESULTS: In total, 10 case-control and 14 cohort studies met the inclusion criteria. Analysis of all studies showed that DM was associated with an increased risk of bladder cancer (RR 1.30, 95% CI 1.18–1.43). There was heterogeneity among studies (P(heterogeneity) <0.001, I(2)=81.5%). Cohort studies showed a lower risk (RR 1.23, 95% CI 1.09–1.37) than case-control studies (odds ratio 1.46, 95% CI 1.20–1.78). The positive association was significant only in women (RR 1.23, 95% CI 1.02–1.49), but not in men (RR 1.07, 95% CI 0.97–1.18). The combined RRs remained unchanged before and after the studies on type 1 diabetes were excluded from analysis. The association between DM and bladder cancer risk did not differ significantly by methods of DM ascertainment. The combined RRs were 1.17 (95% CI 1.03–1.34), 1.34 (95% CI 1.19–1.51), and 1.57 (95% CI 0.96–2.55), respectively, when restricting the analysis to the studies accounting for body mass index, cigarette smoking, or glucose-lowering drug use. CONCLUSIONS: This meta-analysis indicates a positive association between DM and risk of bladder cancer. Further studies are warranted to determine whether DM prevention and control can reduce risk of bladder cancer.